Building side area minimization at the expense of optimization the schedule of movement of workers (rus) - Petrova Ye.M.; Khe Tyanfu; Morozova T.F. (Инженерно-строительный журнал, 2011)
The article analyzes the current methodology of master plan constructing. The requirements of building sides areas minimization in the constrained city conditions lead to the increasing significance of reducing peak values of resource demands in the schedule of movement of workers.The article offers heuristic algorithms and methods to reduce peak loads in the schedule of movement of workers. The algorithm is based on the methods of statistical modeling and involves a limited number of sorting options and choose the best by the criterion of peak values of resources. The method takes into account the mode of dialogue and possibilities of the program MS Project. Techno-economic assessment of proposed optimization solutions master plan is submitted. The proposed calculation method is considered by the example of a business center.